FNAC diagnosis of pleomorphic adenoma of palate - Sudhir Kumar Vujhini; Kandukuri Mahesh Kumar; Konduru Omkareshwar; Sridhar Reddy; Ganesh (MRIMS Journal of Health Sciences, 2014)
Pleomorphic adenoma also called benign mixed tumor, is the most common salivary gland tumor. Most of these tumors occur in major salivary glands; Parotid gland happens to be the commonly involved one (about 90 %) and about 10 % of these occur in the minor salivary glands. The most common sites for pleomorphic adenoma of minor salivary glands are the palate, followed by the lips, the cheeks, floor of the mouth, tongue, tonsil, pharynx, the retromolar area and the nasal cavity. FNAC of intraoral swellings is rarely advised. Here, we are reporting a rare case of pleomorphic adenoma arising from the palate diagnosed on FNA Cytology. We conclude that FNAC is a useful diagnostic tool before surgery even in intraoral swellings.